Dimensional analysis and surface characterisation of ground alumina sintered guide pin / Mahfuzah Zainudin ... [et al.] - Zainudin, Mahfuzah; Arifin, AsyraR; L. Mahmud, Rahimi; Ismail, Muhammad Hussain (UiTM Press for the Research Management Center (IRMI), Universiti Teknologi MARA, 2021)
Alumina (Al2 O3 ) has been considered as satisfactory material used for ceramic guide pin in mechanical engineering applications owing to its excellent properties particularly high strength, good wear and corrosion resistance and extremely low thermal conductivity. However, there is still a major concern with regard to the manufacturing process of the ceramic guide pin, especially in controlling dimensional consistency after the sintering process, leading to part rejection. In this work, the manufacturing of alumina guide pin using powder processing is presented. The focus of this paper is to evaluate dimensional changes and surface analysis of the ground sintered guide pin using an upgraded grinding system. Alumina ceramic guide pin samples were fabricated by a Cold Isostatic Pressure (CIP) technique with four different ranges of diameters known as M6, M8, M10 and M12. All samples underwent sintering process at 1600°C, followed by secondary process by a micro-grinder to remove excessive diameter after sintering. Dimensional measurement was taken using a Vernier calliper, before and after the grinding process for evaluation. The surface roughness of the guide pin was then analysed by a surface roughness analyser followed by morphological analysis by scanning electron microscopy (SEM). From the result obtained, it clearly showed that, the proposed method of post processing using of micro-grinding has worked successfully in reducing numbers of part rejection by the company owing to the inconsistency of dimensional changes after the sintering process. Diameter reduction of about 20 – 50 μm was done for all guide pin models corresponded to the improved surface roughness of Ra, Ry and Rz by 1.3 to 2.0 μm, 8.5 to 11.0 μm and 5.0 to 7.0 μm, respectively. From the SEM analysis, better surface morphology was observed corresponded to surface roughness improvement.